OPTIMALISASI LAPANGAN PENUMPUKAN PETIKEMAS PADA LAHAN TERBATAS TERHADAP KINERJA BONGKAR MUAT.docx - Muhammad Lorenzo; Hendri Dunant Hamidi (LOGISTIK, 2018)
To find out how the process of container stacking field service in order to optimize service to be effective and efficient. In processing goods service at PT. There are 3 types of services provided at Tanjung Priok Port, namely receiving, stacking and loading services. The goods referred to here are containers, services are provided so that the loading and unloading process runs effectively and efficiently.